9,10-Dihydroxy-4,4-dimethyl-5,8-dihydroanthracen-1(4H)-one - Ramírez-Rodríguez, Oney (International Union of Crystallography, 2008)
In the title molecule, C(16)H(16)O(3), the ring system is planar and an intramolecular hydrogen bond is present. The molecular packing is dominated by an intermolecular hydrogen bond and by π-stacking interactions [interplanar separation 3.8012 Å].